2015
DOI: 10.4314/sajas.v45i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Diallel Analysis for Bodyweight Involving Three Genotypes of Nigerian Indigenous Chickens

Abstract: To evaluate heterosis, reciprocal effect, general and specific combining abilities for bodyweight, a diallel crossing experiment was conducted using three genotypes of Nigerian indigenous chickens: normal (N), frizzle (F) and naked-neck (Na). A total of 601 chicks was hatched from all possible matings between the three genotypes. The chicks used in this study were hatched from a foundation stock of 90 chickens comprising 25 hens and 5 cocks for each of the three genotypes. A mating ratio of 1 male : 5 females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
1
8
1
3
Order By: Relevance
“…Our results based on cross for heterosis, the effects for body weights were mostly positive and ranged from -14.11 to 30.07% during different age intervals up to 10 weeks of age. However, Musa et al (2015) reported that heterosis for body weight ranged from -9.44 to 13.48% after crossing three genotypes of Nigerian indigenous chickens. Results of the current study revealed that the P x V cross had encouraging heterosis at all different ages of measurement except at 10 weeks of age when compared to its reciprocal V x P, that had positive heterosis at all ages and highest 10 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results based on cross for heterosis, the effects for body weights were mostly positive and ranged from -14.11 to 30.07% during different age intervals up to 10 weeks of age. However, Musa et al (2015) reported that heterosis for body weight ranged from -9.44 to 13.48% after crossing three genotypes of Nigerian indigenous chickens. Results of the current study revealed that the P x V cross had encouraging heterosis at all different ages of measurement except at 10 weeks of age when compared to its reciprocal V x P, that had positive heterosis at all ages and highest 10 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that Potchefstroom Koekoek sires and Ovambo dams as well as Venda and Venda sires gave the highest heterosis for growth traits. Furthermost reviewed studies showed that body weights of crossbred chickens at different ages were related with negative and positive heterosis effects for growth traits (Sutherland et al, 2018;Musa et al, 2015;Siwendu et al, 2012). However, Nwenya et al (2017) reported a positive heterosis for body weight after crossing Naked neck and Frizzled feather chickens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…지금까지 대표적인 닭의 결합능력 추정에 대한 연구로서 난용종의 계통 간 교배를 이용한 생산능력에 대한 결합능력이나 White Leghorn(WL) 과 Rhode Island Red(RIR)간의 교배와 같이 품종 간 교잡자 손의 산란능력에 대한 결합능력이 보고된 바 있다 (Hill and Nordskog, 1958;Goto and Nordskog, 1959;Wearden et al, 1965Wearden et al, , 1967Ohh et al, 1980Ohh et al, , 1986. 또한 육용계통과 겸용계 통 간의 교배조합이나 국내 토종닭의 계통 간 교배 및 외래 품종 간의 교배조합을 이용한 산육성을 중심으로 한 생산능 력에 대한 결합능력도 보고되었다 (Cheong et al, 1985;Choi, 2002;Mohammed et al, 2005;Saadey et al, 2008;Adebambo et al, 2010Adebambo et al, , 2011Razuki and Al-Shaheen, 2011;Musa et al, 2015). 결합능력 추정 결과들에서 유전력이 높은 체중과 같 은 체 형질의 경우는 상가적 유전효과인 일반결합능력이 주 된 요인으로 작용한 반면, 산란능력과 같은 유전력이 낮은 형질에서는 비상가적 유전효과인 특정결합능력이 상대적으 로 크게 영향을 미치는 것으로 보고하였다.…”
unclassified
“…이러한 결과 는 WL의 계통 간 교배에서 보고한 산란율의 일반결합능력 -8.17∼9.39 및 -9.96∼7.11과 거의 유사한 결과이다 (Ohh et al, 1980(Ohh et al, , 1986. (Ohh et al, 1980(Ohh et al, , 1986, KNC의 계통 간 교잡에서는 -7.31∼14.25로 추정하 et al, 1985;Razuki and Al-Shaheen, 2011;Musa et al, 2015). Table 6은 조합별 시산일령, Table 7은 조합별 난중, Table Table 6.…”
unclassified